Gaya Belajar Mahasiswa D3 Teknik Otomotif Fakultas Teknik Universitas Negeri Padang Tahun Masuk 2016 dan 2017 - Vanny Anreski; Wawan Purwanto; Nurindah Dwiyani (AEEJ : Journal of Automotive Engineering and Vocational Education, 2022)
This study describes the Learning Style of D3 Automotive Engineering Students, Faculty of Engineering, Universitas Negeri Padang. The type of this research is correlational. The research subjects were Automotive Engineering Students, Faculty of Engineering, 2016 and 2017 Entry Years, with 56 students. Data collection techniques include filling out a questionnaire with a Likert scale. This study uses descriptive analysis techniques and confirmatory factors. Based on the confirmatory factor analysis of the results of this study, it can be concluded that the kinesthetic learning style is the most prominent in Automotive Engineering students, Faculty of Engineering, Universitas Negeri Padang, with an average TCR value of 71.76% for the Kinesthetic variable. Penelitian ini bertujuan untuk mendsikripsikan gaya belajar mahasiswa D3 Teknik Otomotif Fakultas Teknik Universitas Negeri Padang. Jenis penelitian yang digunakan oleh peneliti adalah korelasional. Subjek penelitian Mahasiswa Teknik Otomotif Fakultas Teknik Tahun Masuk 2016 dan 2017 dengan jumlah sampel sebanyak 56 mahasiswa. Teknik pengumpulan data dengan mengisi angket dengan teknik pembuatan skala likert. Penelitian ini menggunakan teknik analisis deskriptif dan faktor konfirmatori. Berdasarkan analisis faktor konfirmatori hasil penelitian ini dapat disimpulkan bahwa gaya belajar kinestetik yang paling menonjol pada mahasiswa Teknik Otomotif Fakuktas Teknik Universitas Negeri Padang, dengan nilai TCR rata-rata pada variabel Kinestetik 71.76%.